1965
DOI: 10.1111/j.1748-1716.1965.tb04073.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Nervous Factors Controlling Respiration and Circulation during Exercise Experiments with curarization

Abstract: In the steady state of work on a bicycle ergometer repeated i.v. injections of (+) tubocurarine produced a decrease in handgrip strength. In spite of this the intensity of work was maintained constant for 20 to 30 min. During this time pulse rate and blood pressure increased slightly and irregularity but the ventilation increased, both absolutely and in relation to the oxygen uptake, by up to about 50 %. The cardiac output was uninfluenced by the curarization. By adding CO2 to the inspired air the alveolar PCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(68 citation statements)
references
References 10 publications
5
62
0
Order By: Relevance
“…It has been suggested that during exercise in the heat, central fatigue can occur with progressive hyperthermia, which can reduce arousal and the brain's ability to maintain exercise (30,31). Given that RPE reflects changes in brain activity during prolonged exercise in the heat (33), the increase in V E in this study could in part reflect an increase in central command (1). These thermal and nonthermal factors may operate together during prolonged exercise with progressive hyperthermia and lead to hyperventilation.…”
Section: Discussionmentioning
confidence: 85%
“…It has been suggested that during exercise in the heat, central fatigue can occur with progressive hyperthermia, which can reduce arousal and the brain's ability to maintain exercise (30,31). Given that RPE reflects changes in brain activity during prolonged exercise in the heat (33), the increase in V E in this study could in part reflect an increase in central command (1). These thermal and nonthermal factors may operate together during prolonged exercise with progressive hyperthermia and lead to hyperventilation.…”
Section: Discussionmentioning
confidence: 85%
“…That part of the response initiated from the moving limbs undoubtedly receives an important contribution from the muscle receptors (Alam & Smirk, 1937, 1938 Korner, 1952; Lind, McNicol & Donald, 1966;Coote et al 1971;. Some workers consider that it is the muscle mechanoreceptors that are responsible (Granit, Skoglund & Thesleff, 1953; Gauthier, Lacaisse, Pasquis & Dejours, 1964;Asmussen et al 1965), but there is a strong body of evidence against this (Laporte, Leitner & Pages, 1962; Senapati, 1966;Hodgson & Matthews, 1968; Hnik, Hudlicka, Kucera & Payne, 1969;Coote & Perez-Gonzalez, 1970; Perez-Gonzalez & Coote, 1972;, some of which indicates that it is the small myelinated and unmyelinated nerve fibres of the muscle that are involved.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, earlier experiments involving partial neuromuscular blockade (Ochwadt, Biicherl, Kreuzer & Loeschcke, 1959;Asmussen, Johansen, J0rgensen & Nielsen, 1965;Freyschuss, 1970;BondePetersen, Gollnick, Hansen, Hulten, Kristensen, Secher & Secher, 1975;Secher & Johansen, 1976;Hobbs, 1982) may be of special interest as decamethonium and tubocurarine may preferentially block white and red skeletal muscles, respectively (Paton & Zaimis, 1951;Zaimis, 1953;Jewell & Zaimis, 1954). Also, this preference seems to be valid for humans since a significant correlation has been demonstrated between the degree of curarization and the percentage of slow-twitch muscle fibres in m. vastus lateralis, soleus and gastrocnemius (Secher, Rube & Secher, 1982).…”
Section: Introductionmentioning
confidence: 99%